THEORETICAL AND INSILCO PHARMACOKINETIC INVESTIGATIONS ON SOME PHENYL PIPERIDINE DERIVATIVES AS NOVEL ANTIDEPRESSANT AGENTS - Olasupo Sabitu Babatunde Babatunde; Adamu Uzairu; Gideon Adamu Shallangwa; Sani Uba (The Journal of Engineering and Exact Sciences)
A theoretical bioinformatic investigation was carried out on some Inhibitors of serotonin transporter (SERT) of Phenyl piperidine derivatives using Density Functional Theory (DFT/B3LYP/6-31G*) at ground state with Spartan 14 V1.1.4 software in modeling the antipsychotic activity of the compounds. The molecular descriptors were computed using the PaDEL-Descriptor software 2.20 version. Penta-parametric Multi-linear regression models were developed using the MLR-GFA for selecting the most important descriptors. The statistical parameters for the best model are; R2Train= 0.8572, R 2adj = 0.8274, R2Test = 0.678, Q2cv (LOO) = 0.7664, ?2= 0.0036, r2m (LOO)= 0.694 and Delta r2m (LOO)= 0.0051). Also, the estimated Chi-squared (?2= 0.0036), Root-mean squared error (RMSE= 0.168) and and